Which mango processing residues are suitable for pectin recovery in terms of yield, molecular and techno-functional properties of extractable pectins? - S. Neidhart (2018)
Mimicking industrial pectin recovery, two typical procedures of hot-acid extraction were applied to exemplarily selected mango by-products on a laboratory scale to explore the suitability of the latter in terms of crude and starch-corrected yield, composition as well as molecular and techno-functional properties of the pectins obtained. To exemplify residues from pulp production, fruits of monoembryonic cv. 'Tommy Atkins' at two representative ripeness stages were processed into purées on a pilot-plant scale with recovery of pectins from peels and pulp wastes. With regard to canning and drying waste, pectins from peels of polyembryonic cv. 'Kaew Khiew' were compared to those obtained from the mesocarp, also at two typical ripeness stages. The broad range of recoverable rapid-set to ultra-rapid-set mango pectins with respect to yield, molecular structure, and behaviour was illustrated and compared to commercial non-standardized apple pectin with a similar degree of methylation. Dried mango peels resulted in starch-adjusted yields of ~13% on the average, but the gelling and thickening capacities of peel pectins were limited by a characteristic, almost monodisperse fraction with a peak molecular weight of ~15000-22000 considerably reducing the average molecular weights. From mango pulp, pectins with very good gelling and thickening properties were partly produced, but the yields were insufficient (> 9.3%). For some mango by-products, non-starch neutral sugars limited the galacturonic acid contents to levels below the legal minimum of 65%. Since native starch did not always degrade completely until processing of the fruit, co-extraction of starch partly played a significant role. © Wageningen Academic Publishers. The Netherlands, 2009. All rights reserved.